Poligami dalam Al Quran Perspektif Penafsiran - Nabila Aulia Fitri; Madinatul Zahra; Faturrahman Suryadi; Jendri Jendri (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Polygamy in Islam is permitted under certain conditions, one of which is the obligation to treat wives equally and justly. However, in practice, many instances of polygamy do not align with the noble intentions embedded in Islamic teachings. Polygamy that fails to adhere to the principle of justice can lead to negative impacts on wives, children, and family harmony. These negative effects include violence against women, disruption of family harmony, an increase in divorce rates, and psychological effects on children. Therefore, while polygamy is permitted in Islam, it is essential for the husband to ensure he can fulfill the justice requirements outlined by Islamic law so that the practice of polygamy can bring benefits to all family members. This article discusses the Islamic perspective on polygamy and the negative consequences arising from the practice of polygamy that does not adhere to Islamic teachings.